FAKTOR-FAKTOR YANG MEMENGARUHI MUTU LAYANAN DENGAN TINGKAH LAKU NASABAH - Umbas Krisnanto (University of Merdeka Malang, 2012)
This study was to determine the effect of independent variables quality of service to the dependent variablecustomers behavior. The survey used questionnaires to bank customers. All questionnaires were declared validand reliable. Research idea came from Petridou (2007) and Olorunniwo Hsu (2006) using factor analysisand had variables/dimensions, while Ndubisi (2003) using variables/dimensions was used by Zeithaml (1996).It used regression analysis to compare the quality of service and customer behavior. Conclusions on thedescriptive analysis of respondents stated that the response to the questionnaire on two variables was in therange of excellent category. Factor analysis could not classify variables in shaping a factor. Analysis ofdetermination stated there was a strong and positive relationship between the quality of service and thecustomers behavior amounted to 46.1%. The hypothesis stated that there was relationship in quality of serviceand customer behavior. This research found the value of the variable/dimension was not counted in previousstudies. Suggestions for the bank in the future was enhancing the accuracy and happy to help our customers,and needed to pay attention to social changes. Further research was to find the highest the correlation and morerespondents.